2009
DOI: 10.1242/jcs.046300
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic localization of G proteins in Dictyostelium discoideum

Abstract: Extracellular stimuli exert their effects on eukaryotic cells via serpentine G-protein-coupled receptors and mediate a vast number of physiological responses. Activated receptors stimulate heterotrimeric G-proteins, consisting of three subunits, α, β and γ. In Dictyostelium discoideum, cAMP binds to the cAMP receptor cAR1, which is coupled to the heterotrimer containing the Gα2 subunit. These studies provide in vivo evidence as to how receptors influence the localization of the G-protein complex prior to and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…As discussed below, our analyses suggest Gip1 functions as a regulator of G-protein localization between the cytosol and the plasma membrane. Previous studies have revealed that G proteins undergo translocation to the membrane upon receptor stimulation (17). We found that Gip1 regulates G-protein translocation by its sequestering function (Figs.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…As discussed below, our analyses suggest Gip1 functions as a regulator of G-protein localization between the cytosol and the plasma membrane. Previous studies have revealed that G proteins undergo translocation to the membrane upon receptor stimulation (17). We found that Gip1 regulates G-protein translocation by its sequestering function (Figs.…”
Section: Discussionmentioning
confidence: 57%
“…We next investigated the subcellular localization of G proteins, given that they are modified upon cAMP stimulation (17). Gα2 and Gγ conjugated with the fluorescent dye TMR (Gα2-TMR and TMR-Gγ, respectively) via a Halo tag were used for localization analysis.…”
Section: Uniform Receptor Stimulation Induced Normal Signaling Responmentioning
confidence: 99%
See 2 more Smart Citations
“…In Dictyostelium, a shallow gradient of cAMP induces the activation of cAMP receptors and the associated heterotrimeric G-protein Ga2bc in a manner that is approximately proportional to the steepness of the gradient (Elzie et al, 2009;Jin et al, 2000;Xiao et al, 1997). In contrast, activation of Ras is much stronger in the front than in the rear of chemotaxing cells (Charest et al, 2010;Kortholt et al, 2011;Sasaki et al, 2004;Sasaki and Firtel, 2006;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%